Odpowiedzi

2009-10-29T18:39:55+01:00
2(x-1)+4(x-3)=-3(x-2)+9
2x-2+4x-12=-3x+6+9
-2+6x-12=-3x+15
6x-14=-3x+15
6x+3x=15+14
9x=29 | :9
x= 29/9 =
x=3 cale i 2/9

6(3,5-1,2x)+5(-3,5x+2)+0,3x = 21 - 7,2x - 17,5x +10 +0,3x =

= 31 - 24,7x +0,3x = 31-25x
Najlepsza Odpowiedź!
2009-10-29T18:49:32+01:00
C)
2(x-1)+4(x-3)=-3(x-2)+9x
2x-2+4x-12=-3x+6+9x
2x+4x+3x-9x=6+12+2
0=20

to rownanie ma nieskonczenie wiele rozwiazan
6(3,5-1,2x)+5(-3,5x+1,2)=0,3x
21-7,2x-17,5x-6=0,3x
-7,2x-17,5x-0,3x=6-21
-25x=-15/÷(-25)
x=0.6